A Simply Fabricated Electrochemically Pretreated Glassy Carbon Electrode for Highly Sensitive Determination of Clonazepam by Adsorptive Cathodic Stripping Voltammetry. Issue 5 (19th May 2021) - Khoka, Salinee; Samoson, Kritsada; Yodrak, Janjira; Thiagchanya, Adul; Phonchai, Apichai; Limbut, Warakorn
Abstract : Using a simple method, a glassy carbon electrode was electrochemically pretreated for highly sensitive determination of clonazepam. The electrochemically pretreated glassy carbon electrode was employed as an adsorbent and a working electrode for the detection of clonazepam by adsorptive cathodic stripping voltammetry. The surface morphology and electrochemical properties of the glassy carbon electrode and the electrochemically pretreated glassy carbon electrode were studied by energy dispersive X-ray spectroscopy and cyclic voltammetry. The analytical measurements of clonazepam were evaluated using adsorptive cathodic stripping voltammetry. To obtain the optimal electrochemical reduction of clonazepam by the electrochemically pretreated glassy carbon electrode, the electrochemical pretreatment process, preconcentration potential and preconcentration time were optimized. The detection of clonazepam standards under the optimal conditions produced a cathodic current response with a detection limit of 19 μ g l −1, quantification limit of 63 μ g l −1 and a linear range from 0.0250 to 1.50 mg l −1 . The sensor exhibited excellent sensitivity (453 μ A mg −1 l cm −2 ), and good repeatability (%RSD < 11%) and recovery (98 ± 2 to 102 ± 4%). The developed sensor was successfully utilized for the measurement of clonazepam in beverage samples.